Critical thinking through participatory learning: analysing the nature of freedom of expression in Makerere University lecture theatres - Kimoga, Joseph; Justine, Namaganda; Omar, Abukar Mukhtar; Betty, Anaso; Faith, Kirungi (Advances in Social Sciences Research Journal, 2017)
Participatory learning is the active involvement of the learner in teaching and learning process. It entails participation by all partners in the learning situation. Successful learning outcomes result from supplementing lectures with active learning strategies and engaging students in discovery and scientific processes. Active engagement in learning processes allows students to shape their own learning path and places upon them the responsibility of making their education meaningful. The process shapes their critical thinking, and also places them in better position to critically encounter social, political and economic challenges. This study investigates the nature of learner’s freedom of expression in lecture theatres in Makerere University. Basing on students’ voices, we find that interactions are still very restricted and depriving the right to expression. The study recommends establishing policies that promote learner ownership of interaction, free expression, and change of teacher mind-set.